Leucophyllinines A and B, bisindole alkaloids from Leuconotis eugeniifolia - Tang, Yiming; Nugroho, Alfarius Eko; Hirasawa, Yusuke; Tougan, Takahiro; Horii, Toshihiro; A. Hadi, A. Hamid; Morita, Hiroshi (Springer Verlag (Germany), 2019)
Two new bisindole alkaloids, leucophyllinines A (1) and B (2) consisting of eburnane and quebrachamine-type skeletons were isolated from the bark of Leuconotis eugeniifolia, and their structures were elucidated on the basis of spectroscopic data. Leucophyllinines A and B showed antiplasmodial activities against Plasmodium falciparum 3D7. © 2019, The Japanese Society of Pharmacognosy.